Achieving ideal mentoring: working patterns among clinical instructors, nurses, and nursing students - Ayu Sugiantari; Komang Ayu Kartika Sari; Pande Putu Januraga (Universitas Udayana, 2018)
Background and purpose: The relationships between those responsible for clinical training, clinical instructors (CIs) and nurses, and the nursing students, have a great impact upon student learning during clinical placements. The present study investigates the pattern of working relationships among CIs, nurses, and student nurses, and analyses the extent to which they achieve ideal mentoring practices. Methods: Qualitative study employing in-depth interviews with CIs (n=3), nurses (n=8), and nursing students (n=8) on a clinical placement was undertaken from June-July, 2017, at Badung District Hospital, Denpasar, Bali. Content analysis was conducted to identify the key themes that emerged from these interviews and formed the basis of the findings. The results are presented narratively in order to highlight the patterns of the working relationships identified and perceived by CIs, nurses, and nursing students, with the aim of developing improved mentoring practices. Results: Analysis of the in-depth interviews identified three main themes: (i) perceptions on the hospital’s mentoring practices, (ii) the role(s) and behaviour in the mentoring process, and (iii) the patterns of working relationships between those involved in the mentoring process. In general, participants defined mentoring in terms of the provision of guidance and instruction to students. Participant’s contrasting perceptions of their role(s) affected how they behaved in the mentoring process. Furthermore, participant’s perceptions of their own’s roles and their behaviour provides a detailed overview of the working relationships pattern of the nursing students, nurses and CIs. Specifically, working relationships between CIs and nurses tend to fit an employee-employer type pattern, whereas those between CIs/nurses and nursing students do not appear to reflect typical mentor-mentee relationships. Conclusions: The pattern of working relationships identified between CIs/nurses and nursing students do not, in fact, reflect a typical mentor-mentee relationship. Furthermore, this paper highlights the impact that suboptimal mentoring may have on nursing students’ achievement of medical competence, as well as on the quality of nursing care provided to patients in teaching hospitals.